Recent advances in fabrication of dECM-based composite materials for skin tissue engineering - Xu, Peiyao; Cao, Jiutao; Duan, Youyu; Kankala, Ranjith Kumar; Chen, Aizheng (Frontiers in Bioengineering and Biotechnology, 2024)
Chronic wound management is an intractable medical and social problem, affecting the health of millions worldwide. Decellularized extracellular matrix (dECM)-based materials possess remarkable biological properties for tissue regeneration, which have been used as commercial products for skin regeneration in clinics. However, the complex external environment and the longer chronic wound-healing process hinder the application of pure dECM materials. dECM-based composite materials are constructed to promote the healing process of different wounds, showing noteworthy functions, such as anti-microbial activity and suitable degradability. Moreover, fabrication technologies for designing wound dressings with various forms have expanded the application of dECM-based composite materials. This review provides a summary of the recent fabrication technologies for building dECM-based composite materials, highlighting advances in dECM-based molded hydrogels, electrospun fibers, and bio-printed scaffolds in managing wounds.The associated challenges and prospects in the clinical application of dECM-based composite materials for wound healing are finally discussed.